2016
DOI: 10.1128/jvi.00915-16
|View full text |Cite
|
Sign up to set email alerts
|

Exocytosis of Varicella-Zoster Virus Virions Involves a Convergence of Endosomal and Autophagy Pathways

Abstract: Varicella-zoster virus (VZV) is an extremely cell-associated herpesvirus with limited egress of viral particles. The induction of autophagy in VZV-infected monolayers is easily detectable; inhibition of autophagy leads to decreased VZV glycoprotein biosynthesis and diminished viral titers. To explain how autophagic flux could exert a proviral effect on the VZV infectious cycle, we postulated that the VZV exocytosis pathway following secondary envelopment may converge with the autophagy pathway. This hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 75 publications
4
66
0
Order By: Relevance
“…Even though it suggests that this subject may be showing some type of persistent, asymptomatic infection, with the positive staining seen by confocal microscopy one would assume that this would be detectable by PCR. Although there is strong evidence to the specificity of the antibody used for VZV with no cross‐reactivity to other viruses, this does not eliminate the possibility of cross‐reactivity with other viruses which may provide an explanation of the results obtained. Some studies have even suggested non‐specific staining of VZV by confocal microscopy in dying cells (Chuck Grose, personal communication).…”
Section: Discussionmentioning
confidence: 88%
“…Even though it suggests that this subject may be showing some type of persistent, asymptomatic infection, with the positive staining seen by confocal microscopy one would assume that this would be detectable by PCR. Although there is strong evidence to the specificity of the antibody used for VZV with no cross‐reactivity to other viruses, this does not eliminate the possibility of cross‐reactivity with other viruses which may provide an explanation of the results obtained. Some studies have even suggested non‐specific staining of VZV by confocal microscopy in dying cells (Chuck Grose, personal communication).…”
Section: Discussionmentioning
confidence: 88%
“…Taken together, the results show that the autophagic endosomal pathway is one mechanism that facilitates IBDV maturation, release, and reinternalization. A recent study claims that a subpopulation varicella-zoster virus particles are sorted into a vesicle resembling an amphisome for their final trafficking to the outer cell membrane (33). Overall, these researches suggest that highly divergent DNA and RNA viruses may share similar exit pathways.…”
Section: Figmentioning
confidence: 95%
“…However, the mechanism of viral maturation and release needs further investigation. A recent study indicated that exocytosis of varicella-zoster virus virions involves a convergence of endosomal and autophagy pathways (33). The investigators demonstrated that some viral particles after secondary envelopment accumulated in a heterogeneous population of single-membraned vesicular compartments, which were decorated with components from both the endocytic pathway (Rab11) and the autophagy pathway (LC3B).…”
mentioning
confidence: 99%
“…A typical VZV replication cycle consists of the following steps: virus entry and uncoating, viral gene expression and genome replication, nucleocapsid assembly and egress from nucleus to cytoplasm, virion assembly in the Golgi apparatus, and virion release and transcellular transmission from host cell to neighboring cells (8)(9)(10). The VZV genome encodes at least 20 tegument proteins with regulatory function or tegumentation (11).…”
mentioning
confidence: 99%